30 AÑOS DE LA CONFERENCIA INTERNACIONAL DE POBLACIÓN Y DESARROLLOEN EL CAIRO: AVANCES Y DESAFÍOS EN LOS DERECHOS REPRODUCTIVOS - Guevara Ríos, Enrique (2024)
From September 5 to 13, 1994, the International Conference on Population and Development (ICPD) was held in Cairo, marking a historic event in the advancement of human rights. This conference triggered a global shift in population and development strategies, reflected in the adoption of a Programme of Action that emphasized the prioritization of reproductive rights and the empowerment of girls, adolescents, and women worldwide. This approach also highlighted the importance of addressing inequalities and the needs, aspirations, and rights of these populations. Only through this commitment can truly sustainable and inclusive development be achieved.